ANALISIS TINGKAT KESEHATAN BANK DENGAN MENGGUNAKAN RASIO CAMEL (STUDI KASUS PADA BANK RAKYAT INDONESIA (PERSERO) TBK) - Makmur., Hendra Saputra, Andi Afrizal, (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2017)
The purpose of this study was to determine the financial soundness of the Bank are measured by CAMEL analysis at Bank Rakyat Indonesia (Persero) Tbk, to determine the financial soundness of the Bank at Bank Rakyat Indonesia (Persero) Tbk. In analyzing the data used descriptive method quantitative data obtained and analyzed on the basis of the existing theory so as to provide an overview and calculations are quite clear. By doing a comparison between the theories used in research with application in the enterprise, then arranged in a manner to be analyzed carefully and then made conclusions. Based on the results of the study showed that the financial soundness of the Bank Rakyat Indonesia (Persero) Tbk HEALTHY declared 2010-2014 to be reviewed through rasiop CAMEL, CAMEL ratio is capital, assets, management, earnings, and liquidity is a ratio used by the author in analyzing the level health at Bank Rakyat Indonesia (Persero) Tbk standard berdasaarkan Bank Indonesia. In the capital, aspects of asset quality and profitability aspects comprising BOPO and ROA ratios in 2010-2014 is said to be HEALTHY while in aspects of management in 2011-2014 and in 2010 said HEALTHY HEALTHY say ENOUGH and the liquidity aspect of 2010-2012 and 2014 is said to be healthy and in 2013 said HEALTHY ENOUGH by the standards of Bank Indonesia.